MECHANISMS OF INCREASING LISTENING SKILLS IN LANGUAGE TEACHING - Norqulova , Shaxlo Jasurbekovna (GOLDEN BRAIN, 2024)
This article is devoted to methods of formation of students' listening ability. Linguistic forecasting is facilitated by the skill of combining words. Knowing the rules of combinability of lexical units, students are more and less likely to be able to predict the content of incoming information, since the combinability of words in the language is limited.